Nutritional Values of Partially Replacing the Commercial Soybean Meal by Raw, Full-Fat Soybean in Diets of Layers - Mammo Mengesha Erdaw; Shambel Taye (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to investigating the effects of partially replacing the commercial soybean meal (SBM) by locally produced raw, full-fat soybean (RFFSB) in diets of layers. After cleaning, the tested ingredient (RFFSB) was hammered to pass through a 0.2-mm sieve. Then, four experimental diets were formulated by replacing the SBM by RFFSB at 0, 15, 30 or 45% (equivalents to 0, 30, 60 or 90 g/kg of diet, respectively). Before the commencement of this feeding trial, birds were uniformly managed and fed as per their requirements (i.e., starter, grower and pullet diets). This feeding trial was started when birds’ age was 24 weeks. Every treatment was replicated 4 times and 17 laying birds per replicate. The results revealed that replacing the commercial SBM by raw soybean (up to 45%) in the layer diets had no negative effects on the final live BWT and also on the vital organ developments, such as pancreas, duodenum, intestines and gizzard. Hen-day egg production, hen-housed egg production and egg quality measuring parameters were not significant affected by that of partially replacing the commercially SBM by the raw soybean. It is concluded that without compromising the productivity and health, a hammered RFFSB can replace (up to 45%) the commercial SBM in diets of the laying hens.